SISTEM PENGETAHUAN NELAYAN TERHADAP KESEHATAN IBU DAN ANAK DI NAGARI PASAR LAMA MUARA AIR HAJI, KECAMATAN LINGGO SARI BAGANTI, KABUPATEN PESISIR SELATAN - Yunarti - - (Universitas Andalas, 2015)
A high level of knowledge in society will increase the level of participation, especially the participation of health. This impact on cultural behavior of public health, especially maternal and child health issues have started well. Most of the mothers in the Pasar Lama Muara Air Haji village already have a system of knowledge that is high enough on the problem of health care of pregnant women and their children. This is also supported by the role of midwives and health volunteers help disseminate health through education programs and integrated health services